2017
DOI: 10.1111/add.13928
|View full text |Cite
|
Sign up to set email alerts
|

Effects of comorbid substance use disorders on outcomes in a Housing First intervention for homeless people with mental illness

Abstract: Housing First programs in Canada are equally effective in people with and without comorbid substance use disorder (SUD). Overall, the intervention appears to be able to engage people with SUD and is reasonably successful at housing them, without housing being contingent upon abstinence or treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
85
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(89 citation statements)
references
References 43 publications
4
85
0
Order By: Relevance
“…Two decades of research have consistently shown that Housing First is effective in helping many people experiencing homelessness to achieve stable housing (Aubry et al, 2020; Baxter, Tweed, Katikireddi, & Thomson, 2019; Padgett, Henwood, & Tsemberis, 2016). Similar housing stability outcomes have also been found for various homeless adult subpopulations, including people with problematic substance use (e.g., Adair et al, 2017; Cherner, Aubry, Sylvestre, Boyd, & Pettey, 2017; Padgett, Gulcur, & Tsemberis, 2006; Tsemberis, Gulcur, & Nakae, 2004; Urbanoski et al, 2018).…”
Section: Introductionsupporting
confidence: 53%
“…Two decades of research have consistently shown that Housing First is effective in helping many people experiencing homelessness to achieve stable housing (Aubry et al, 2020; Baxter, Tweed, Katikireddi, & Thomson, 2019; Padgett, Henwood, & Tsemberis, 2016). Similar housing stability outcomes have also been found for various homeless adult subpopulations, including people with problematic substance use (e.g., Adair et al, 2017; Cherner, Aubry, Sylvestre, Boyd, & Pettey, 2017; Padgett, Gulcur, & Tsemberis, 2006; Tsemberis, Gulcur, & Nakae, 2004; Urbanoski et al, 2018).…”
Section: Introductionsupporting
confidence: 53%
“…In this sense, the care for this user profile may not be only oriented towards the use itself, but should also act on the subjects' basic needs, as envisaged in the CAPS as work in territorial coordination. International programs known as "housing first" have been efficient in treating addictive disorders for those cases, and what is most interesting is that good results happen regardless of abstinence (13) . When admitted to the beds, 87.6% subjects used multiple substances daily, specially alcohol (77%), crack (60%), and cocaine (48.1%).…”
Section: Discussionmentioning
confidence: 99%
“…Some evidence, cited by Urbanoski et al . , suggests that two of the main variants of Housing First, i.e. those offering assertive community treatment (ACT) and intensive case management (ICM) and those following an ICM‐only approach, do not differ significantly in terms of outcomes.…”
Section: Declaration Of Interestsmentioning
confidence: 99%